1984
DOI: 10.1001/archinte.144.4.715
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of synovial fluid analysis in the evaluation of joint effusions. Use of threshold analysis and likelihood ratios to assess a diagnostic test

Abstract: This study applied threshold analysis and likelihood ratios to determine the usefulness of a diagnostic test. Eleven staff rheumatologists or rheumatology fellows provided probability estimates for the most likely diagnoses both before and after synovial fluid analyses were performed on 180 patients with joint effusions. They also indicated whether the planned therapy was altered by the test results. The therapeutic thresholds and log likelihood ratios were derived for the six most frequent diagnoses. Synovial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…The derived therapeutic thresholds were consistent with recommended medical practice, for example, with a lower threshold for possible septic arthritis (20%) than for possible gout (65%). 6 Findings of the present study suggest that 83.3% patients of osteoarthritis had ESR 20 mm/hr moreover Serum RF and CRP were positive in 8.3% and 13.3% respectively. These findings correlate well with suggestion by Sipe that there is a modest rise in ESR and the concentration of CRP are elevated in osteoarthritis but to a lesser extent than rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 44%
“…The derived therapeutic thresholds were consistent with recommended medical practice, for example, with a lower threshold for possible septic arthritis (20%) than for possible gout (65%). 6 Findings of the present study suggest that 83.3% patients of osteoarthritis had ESR 20 mm/hr moreover Serum RF and CRP were positive in 8.3% and 13.3% respectively. These findings correlate well with suggestion by Sipe that there is a modest rise in ESR and the concentration of CRP are elevated in osteoarthritis but to a lesser extent than rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 44%
“…3 4 It was subsequently shown that detection of crystals in SF may change clinical diagnosis and treatment. 5 Moreover, analysis of aspirated joint fluid is regarded as the key to the diagnosis of infectious arthritis. The analysis of SF is recommended by textbooks and publications as an important aid to diagnosis.…”
mentioning
confidence: 99%
“…28 In some clinical laboratories, SF differential counts are omitted when total cell counts are less than 1,000/ mm ' . 3,28,29 In a recent publication regarding TS staining in "noninflammatory" fluids with less than 2,000 cells Lymphocytes and fibrin strands in the synovial fluid of a patient with seronegative spondyloarthropathy (cresyl violet and methylene blue X 1000).…”
Section: Discussionmentioning
confidence: 99%